Investigating the complexity of consent forms in ESL research. (12th July 2018) - Sterling, Scott
Abstract : Consent forms tell potential participants what to expect when joining a research project and are considered critical documents to the research process. However, there has been limited investigation into how to properly create a usable consent form for ESL learners. Most of our current knowledge on the topic comes from various governmental mandates, rules of thumb, or from fields outside of linguistics or TESOL research. This paper details an investigation looking into the practices of consent form writing in 40 published ESL-based dissertations. Findings show that the average consent form was around 2.38 pages long and written above the 11th grade level. Additionally, vocabulary from the forms included a large representation of infrequent words that might not be known by ESL participants. Consent forms written for ESL participants appear to be highly complex documents with their difficulty unlikely to provide truly informed consent. A troubling finding since these researchers could be considered experts in understanding ESL learner needs.